2022
DOI: 10.3390/galaxies10030066
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Ray Bursts Afterglow Physics and the VHE Domain

Abstract: Afterglow radiation in gamma-ray bursts (GRB), extending from the radio band to GeV energies, is produced as a result of the interaction between the relativistic jet and the ambient medium. Although in general the origin of the emission is robustly identified as synchrotron radiation from the shock-accelerated electrons, many aspects remain poorly constrained, such as the role of inverse Compton emission, the particle acceleration mechanism, the properties of the environment and of the GRB jet itself. The exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 186 publications
0
14
0
Order By: Relevance
“…Furthermore, observations of prompt and afterglow emission from both long and short GRBs provide unique insights into the physics of energy transport and dissipation within relativistic jets (see e.g., Kumar & Zhang 2015; Miceli & Nava 2022 for review articles). For example, the very recent opening of the so-called VHE (Very High Energy) window, with the detection of TeV emission from GRB afterglows (MAGIC Collaboration et al 2019; Abdalla et al 2019; H.E.S.S.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, observations of prompt and afterglow emission from both long and short GRBs provide unique insights into the physics of energy transport and dissipation within relativistic jets (see e.g., Kumar & Zhang 2015; Miceli & Nava 2022 for review articles). For example, the very recent opening of the so-called VHE (Very High Energy) window, with the detection of TeV emission from GRB afterglows (MAGIC Collaboration et al 2019; Abdalla et al 2019; H.E.S.S.…”
Section: Introductionmentioning
confidence: 99%
“…This process is a natural by-product of the classical synchrotronemission model, and can account for emission in this energy band. However, it is not clear yet whether this model can explain the broadband data (at all wavelengths), given the strong constraints on the TeV band flux from radio, optical, and X-ray data (González et al 2023;Miceli & Nava 2022). Furthermore, this model cannot explain the 10 TeV energy photons (Huang et al 2022) originally claimed to be observed (González et al 2023;Ren et al 2023;Laskar et al 2023a;Das & Razzaque 2023;Kann et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The prompt phase is then followed by an extended broadband afterglow, detected at all energy bands, from radio to a few hundreds of GeVs and possibly even higher (for reviews, see, e.g., Piran 1999;Mészáros 2006;Kumar & Zhang 2015;Zhang 2018). Detections of GRB afterglows at the highest energies (i.e., >300 GeV) have been on the rise in the past two decades (for reviews, see, e.g., Nava 2018;Miceli & Nava 2022). Understanding the physics underlying this emission has become of highest importance as it holds clues to better constrain and understand the afterglow of GRBs.…”
Section: Introductionmentioning
confidence: 99%
“…Gamma-ray bursts (GRBs) are among the most luminous explosions in the universe (Mészáros 2006;Kumar & Zhang 2014). In 2019, the detection of two TeV bursts, GRB 190114C (MAGIC Collaboration et al 2019;MAGIC Collaboration 2019) and GRB 180720B (Abdalla et al 2019), opened a new window in the very high-energy (VHE)(0.1 TeV) band for studying GRBs, providing us with new opportunities to investigate the nature of GRBs (see Gill &Granot 2022 andMiceli &Nava 2022 for reviews).…”
Section: Introductionmentioning
confidence: 99%